ANALYSIS OF JOB CRAFTING ON ADMINISTRATION DIVISION AT PT. HM SAMPOERNAH TBK. MANADO - Soetanto, Kezia; Tumbuan, Willem J. F. A.; Pandowo, Merinda H.C. (Universitas Sam Ratulangi, 2020)
Job crafting is the process where the employees implement their ability to work better, to gain more experiences by doing new things and improving their skills as an employee to work better. Job crafting may help the employees to explore their abilities. This study aims to analyze the job crafting on the administration division. To achieve these objectives the researcher got information from 10 respondents using a qualitative study which is in-depth interviews and uses purposive sampling. The result shows that Job crafting that has been done by every employee has a positives influence on employee outcomes. The job crafting helps all the employees to become more productive to work, and also the job crafting might help the employees to finish their work faster. Job crafting is become very helpful and useful to the all-employee, because doing the job crafting its effective to help the employee to grow better, and job crafting affects the employment outcomes and become one of the important roles for the employees. One of the recommendations of this research is PT. HM Sampoerna should use or let the employee do job crafting so that it can increase the effectiveness of their work.Â Keywords: job crafting, human resources